Pourquoi consommer la viande de brousse ? Réponses auprès des populations de Yangambi et de Kisangani, République Démocratique du Congo - Olivier Igugu; Theodore Tréfon (VertigO)
Bushmeat is an essential element in the diet and culture of tropical forest populations. Apart from species prohibited by custom, all species are consumed. In our study sites, bushmeat consumption is decreasing. Population growth, used hunting techniques and deforestation are the main explanations for the decline in wildlife resources in the area. The forest of Yangambi, which was the reservoir of bushmeat consumed by the inhabitants of this city as well as those of the city of Kisangani, is becoming an “empty forest”. Faced with this scarcity and the absence of other sources of animal protein, the population is faced with food challenges. However, the population remains attached to the consumption of bushmeat for many reasons. This study presents an analysis of these reasons, including socio-cultural dimensions. Each individual, family, clan or tribe has a particular relationship with bushmeat. This relationship is dynamic, and the motivations of the past are not necessarily those of today and will probably not be those of tomorrow. The local perception is that bushmeat is a food before it is a conservation priority. Finally, it appears that the observance of dietary prohibitions, which favored conservation in the past, is now less and less respected.